An antigen receptor-driven, interleukin 2-independent pathway for proliferation of murine cytolytic T lymphocyte clones (The Rockefeller University Press, 1986)
Proliferation of T lymphocytes can be induced by IL-2, either through an autocrine pathway in which the responding cell produces its own IL-2 or through an exocrine pathway in which IL-2 secreted by Th stimulates proliferation of IL-2-dependent CTL. However, proliferation of at least some CTL clones, such as CTL L3 and CTL dB45, also can be induced by stimulation of the antigen receptor in the absence of IL-2. Stimulation of these cloned CTL with T cell-depleted allogeneic spleen cells, allogeneic tumor cells, or immobilized mAb reactive with the T cell antigen receptor (TCR) induced thymidine incorporation, entry into cell cycle, and secretion of macrophage activating factor, but these stimuli did not induce the secretion of IL-2. Several observations indicated that such proliferation of cloned CTL induced by stimulation of the TCR was independent of IL-2; IL-2 could not be detected in supernatants from stimulated CTL cells. mAbs reactive with the murine IL-2-R efficiently blocked IL-2-mediated thymidine incorporation in cloned CTL and Th, but had no inhibitory effect on TCR-driven thymidine incorporation in the CTL clones. TCR-driven thymidine incorporation in cloned Th L2 cells was profoundly inhibited by these antibodies, indicating the operation of an IL-2-mediated autocrine pathway for proliferation in this cloned Th. When antibodies to the TCR were used to stimulate cloned CTL and Th, IFN-gamma mRNA was easily shown in the cloned CTL and Th. Although IL-2 mRNA could be detected in the cloned Th, it was never observed in the cloned CTL. These findings provide evidence for the existence of a TCR-mediated, IL-2-independent pathway for induction of cellular proliferation in cloned murine CTL.